Hak-hak Asasi Manusia: Perspektif Al-Qur’an - Yusron Razak (Refleksi: Jurnal Kajian Agama dan Filsafat, 2003)
In 1948, the United Nations (UN) issued the Universal Declaration of Human Rights (UDHR), a significant document that sets universal standards for the respect and protection of the fundamental rights of every individual regardless of race, color, religion, gender, language, or other statuses. From the perspective of the Qur’an, the concept of human rights can be found in various verses that emphasize human dignity, justice, and equality. The Qur’an, as the holy book of Islam, teaches that all humans are created by Allah with inherent dignity and must be treated with justice and respect. Qur’anic verses such as Surah Al-Hujurat (49:13), which states that humanity was created in different tribes and nations to know and respect each other, and Surah An-Nisa’ (4:135), which commands Muslims to uphold justice even against themselves or close relatives, illustrate fundamental principles aligned with the UDHR. This study aims to identify and analyze the alignment between the UDHR and the teachings of the Qur’an regarding human rights. By examining Qur’anic verses and interpretations from scholars, this research will highlight how the concept of human rights in Islam can support and enrich the global understanding of human rights. Furthermore, this study will address the challenges and opportunities in integrating universal human rights values with Sharia principles and their implications for Muslim communities worldwide. Through an interdisciplinary approach, this abstract offers deep insights into the relationship between the sacred text of the Qur’an and international human rights standards, paving the way for better dialogue and understanding in the future.